2001
DOI: 10.1023/a:1011158021749
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Human T-cell leukemia virus type I (HTLV-I) is the etiologic agent of adult T-cell leukemia (ATL), which is an aggressive form of human T-cell malignancy. The viral protein, Tax, immortalizes human T-cells and inhibits various types of apoptosis, and is thought to play crucial roles in the development of ATL. We have recently demonstrated that Tax induces the constitutive expression of the anti-apoptotic protein, Bcl-xL, in a mouse T-cell line. The mouse, however, is not a natural host of HTLV-I, and HTLV-I do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…Previous reports demonstrated that NF-kB is an important transcriptional regulator of Bcl-2 and Bcl-XL (Mori et al, 2001;Sevilla et al, 2001;Bharti and Aggarwal, 2002;Beinke and Ley, 2004;Panwalkar et al, 2004). NF-kB is a family of transcription factors composed of homo-and heterodimers of Rel family polypeptides: p50, p52, RelA (p65), RelB and c-Rel (Rel) (Bharti and Aggarwal, 2002;Beinke and Ley, 2004;Panwalkar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that NF-kB is an important transcriptional regulator of Bcl-2 and Bcl-XL (Mori et al, 2001;Sevilla et al, 2001;Bharti and Aggarwal, 2002;Beinke and Ley, 2004;Panwalkar et al, 2004). NF-kB is a family of transcription factors composed of homo-and heterodimers of Rel family polypeptides: p50, p52, RelA (p65), RelB and c-Rel (Rel) (Bharti and Aggarwal, 2002;Beinke and Ley, 2004;Panwalkar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The induction of NF-kB by Ras was mediated by two pathways involving both Raf and PI3-kinase leading to the activation of the IKK complex (Arsura et al, 2000). Importantly, many other tumors have recently been shown to display constitutive activation of NF-kB (reviewed in Rayet and Gelinas, 1999), including the human cutaneous T-cell lymphoma HuT-78 (Giri and Aggarwal, 1998), Hodgkin's lymphomas (Bargou et al, 1997), melanoma (Shattuck et al, 1994) pancreatic adenocarcinoma (Wang et al, 1999), primary adult T-cell leukemia (Mori et al, 1999), and head and neck squamous cell carcinoma (Du ey et al, 1999). Furthermore, the Tax transforming protein produced by the human T-cell leukemia virus type 1 induces NF-kB activity (Mercurio et al, 1997;Sun et al, 1994) through activation of both IKK1 and IKK2 (Geleziunas et al, 1998;Sumitomo et al, 1999b).…”
Section: Discussionmentioning
confidence: 99%
“…ATL cells that do not express Tax also have an activated NF-kB pathway, although the mechanism of activation remains unknown (Mori et al, 1999). From this point of view, suppression of NF-kB pathway might be a good therapeutic target against ATL.…”
Section: Treatment Of Atlmentioning
confidence: 99%